Answer:
length is (-7,-1) and radius is 6
Step-by-step explanation:
We are given the expression of the equation of a circle that is
x2 + y2 + 14x + 2y + 14 = 0.
Using completing the squares:
x2 + y2 + 14x + 2y + 14 = 0(x+7)^2 + (y+1) ^2 = -14 + 49 + 1(x+7)^2 + (y+1) ^2 = 36 center thus is at (-7,-1) and the radius is equal to square root of 36 equal to 6.
S (3, 0)
C (5, 1)
W (4, -4)
Explanation
You take the first number and add 6 to it and you get the new number and then you take the second number and subtract 3 from it
S: -3 + 6 = 3
S- 3 - 3 = 0
C: -1 + 6 = 5
C: 4 - 3 = 1
W: -2 + 6 = 4
W: -1 - 3 = -4
It’s 5,905 bc you need to add all of you distilled water to know if you have enough
12 people ⇒8 cups
1 person ⇒ 8/12 = 2/3 cup
7 persons ⇒ 2/3 x 7 = 14/3 4 2/3 cups
Answer: She should use 4 2/3 cups of sugar.
Consider the operation is
.
Given:
The augmented matrix below represents a system of equations.
![\left[\left.\begin{matrix}1&0&1\\1&3&-1\\3&2&0\end{matrix}\right|\begin{matrix}-1\\-9\\-2\end{matrix}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cleft.%5Cbegin%7Bmatrix%7D1%260%261%5C%5C1%263%26-1%5C%5C3%262%260%5Cend%7Bmatrix%7D%5Cright%7C%5Cbegin%7Bmatrix%7D-1%5C%5C-9%5C%5C-2%5Cend%7Bmatrix%7D%5Cright%5D)
To find:
Matrix results from the operation
.
Step-by-step explanation:
We have,
![\left[\left.\begin{matrix}1&0&1\\1&3&-1\\3&2&0\end{matrix}\right|\begin{matrix}-1\\-9\\-2\end{matrix}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cleft.%5Cbegin%7Bmatrix%7D1%260%261%5C%5C1%263%26-1%5C%5C3%262%260%5Cend%7Bmatrix%7D%5Cright%7C%5Cbegin%7Bmatrix%7D-1%5C%5C-9%5C%5C-2%5Cend%7Bmatrix%7D%5Cright%5D)
After applying
, we get
![\left[\left.\begin{matrix}1&0&1\\-3(1)&-3(3)&-3(-1)\\3&2&0\end{matrix}\right|\begin{matrix}-1\\-3(-9)\\-2\end{matrix}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cleft.%5Cbegin%7Bmatrix%7D1%260%261%5C%5C-3%281%29%26-3%283%29%26-3%28-1%29%5C%5C3%262%260%5Cend%7Bmatrix%7D%5Cright%7C%5Cbegin%7Bmatrix%7D-1%5C%5C-3%28-9%29%5C%5C-2%5Cend%7Bmatrix%7D%5Cright%5D)
![\left[\left.\begin{matrix}1&0&1\\-3&-9&3\\3&2&0\end{matrix}\right|\begin{matrix}-1\\27\\-2\end{matrix}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cleft.%5Cbegin%7Bmatrix%7D1%260%261%5C%5C-3%26-9%263%5C%5C3%262%260%5Cend%7Bmatrix%7D%5Cright%7C%5Cbegin%7Bmatrix%7D-1%5C%5C27%5C%5C-2%5Cend%7Bmatrix%7D%5Cright%5D)
Therefore, the correct option is A.